Towards understanding the structural adaptations within the Bangladesh handloom industry: 1978-1987 - Chowdhury, Nuimuddin; Latif, Muhammad Abdul (Dhakka : Bangladesh Unnayan Gobeshona Protishthan, 1990)
The objective of BHSS is to assess the entire handloom industry in Bangladesh in terms of various techno-economic and structural characteristics, to identify the major strengths and weaknesses of the industry and to make proposals for the development of the industry.
Includes bibliographical references.
rpm 22/01/2019
Loans
Keywords: Handloom industry; Labor supply; Wages